(3JfRjg GdCfHjGAs - (3GdMSjfj GdbQTj, CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, (B436 (3g`s ((3eMeO UGdM Hf YHO GdQShd Hf eMeO MSjf Hf MSf GdNQSGfjs)
(3ChdgG (B:s
(3GdMeO ddg ceG gh Cgdg (B... (3GedGA cJGH aj JfRjg GdCfHjGA hGdCFeI Ydjge GdSdGe Yf GdPfhH hGdbHGFM cdgG eG Sej efgG cHjQG hUZjQG hGdQO Ydi ef NGda aj Pdc Ydi GNJdGage hVQhH ePGgHge (B...s
(3BNQgG (B:s
.. (3hbO ChQOfG efg GdcKjQ aj cJGHfG aj GdEeGeI hdYdfG fSJbUj GdcdGe ajg hjCJj Ydi eG dYdg de fhQOg aj cJGH GdEeGeI aj ehVY faQOg dg (B... (3hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B4/ 278s
(3GdPQjYI (B4\2023s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds